On Language, Translation and Comparative Stylistics - Brini, Hafedh (Meta, 2000)
AbstractThis paper aims to show the complex relations between three components: language, translation and comparative stylistics in a context of teaching foreign languages. These different subjects should not be confused; they should rather be designed and organized according to their individual aims as well as their collective objectives, so that we may keep pace with the progress made in these fields.